A note on a singular coupled burgers equation and double laplace transform method - Kilicman, Adem; Eltayeb, Hassan; Mesloub, Said (International Scientific Research Publications, 2018)
In this paper, modification of double Laplace decomposition method is proposed for the analytical approximation solution of a coupled system of Burgers equation with appropriate initial conditions. Some examples are given to support the validity and applicability of the presented method.